Expression and ultrastructural localization of plasmin(ogen) in the terminally differentiated layers of normal human epidermis. (20th November 2019) - Voegeli, R.; Rawlings, A.V.; Haftek, M.
Abstract: Objective: Plasmin, a relatively unspecific trypsin‐like serine protease, is involved in many physiological and pathological conditions, particularly in dermatoses with barrier impairment. It is secreted as the inactive zymogen plasminogen and is activated to plasmin by plasminogen activators, such as urokinase. There still exists a paucity of data on the precise localization of epidermal plasmin(ogen) within the epidermis and the stratum corneum. The aim of the present study was to get information about its origin and ultrastructural localization within normal human epidermis. Method: We performed immunoelectron transmission electron microscopy immunogold labelling in normal abdominal human skin. Result: Plasmin was only observed in the terminally differentiated cell layers of the epidermis and was largely associated with the corneocyte envelopes and to some extent with the intercellular lipid matrix in the stratum corneum. Conclusion: Our results indicate that in normal human skin, plasmin(ogen) is synthesized by differentiated epidermal keratinocytes of the stratum granulosum and is not serum‐born. Abstract : There exists a paucity of data on the subcellular localization of plasmin(ogen) within normal human epidermis. Immunoelectron transmission electron microscopy labelling revealed that the inflammatory serine protease is located in the terminally differentiated keratinocytes and was largely associated with the corneocyte envelopes and to some extent with the intercellular lipid matrix in the stratum corneum. Résumé: Objectif: Plasmine, une relativement peu spécifique ' trypsin‐like' protéase sérine, participe aux plusieurs processus physiologiques et pathologiques et, plus particulièrement, à la physiopathologie des dermatoses caractérisées par l'altération de la barrière de perméabilité. Elle est sécrétée sous forme d'un zymogene inactif, plasminogène, et devient activée par les activateurs du plasminogène, telle urokinase. A l'heure actuelle, on manque de précision quant à la localisation de plasmine (ou son précurseur) dans l'épiderme et le stratum corneum. Le but du présent travail a été de d'apporter l'information sur la provenance et la localisation ultrastructurale de plasmine/plasminogène présents dans l'épiderme humain. Méthode: L'étude ultrastructurale de l'épiderme humain normal (plastie abdominale) a fait appel à l'immunomarquage à l'or colloïdal sur coupes ultrafines des tissus inclus à froid dans des résines acryliques. Résultat: L'anticorps monoclonal anti –plasmine/plasminogène a détecté l'antigène situé exclusivement dans la partie la plus différenciée de l'épiderme et persistant dans la couche cornée. Il n'y a pas eu de réactivité dans les couches épineuse et basale. Le marquage a été prédominant sur les enveloppes cornifiées des kératinocytes granuleux et cornéocytes. Des foyers du marquage ont été également présents dans le cytoplasme et les espaces intercellulaires de la couche granuleuse, ainsi que dans la matrice lipidique de la couche cornée profonde. Conclusion: Nos résultats indiquent la production de novo de plasmine/plasminogène dans les kératinocytes le plus différenciés et ne suggèrent pas l'origine sérique de cette enzyme dans l'épiderme.